CHRONIC RHINOSINUSITIS: PATHOPHYSIOLOGY, DIAGNOSIS, AND EVIDENCE-BASED TREATMENT (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The article discusses current concepts of chronic inflammation of the paranasal sinuses in children (chronic rhinosinusitis, CRS) based on the European Position Paper on Rhinosinusitis and Nasal Polyps 2012 (EPOS 2012). The structure of bacterial pathogens, trigger factors of CRS, and modern treatment recommendations are presented. Special attention is given to the use of topical antibacterial therapy, particularly fusafungine (Bioparox), in children over 12 years of age with CRS.